Short-term clinical outcomes of kidney paired donation in living donor kidney transplants: a retrospective study - Bashir, Asad; Minallah, Nasrum; Touqeer, Fiaz Ahmad; Akram, Zia Ul Haq; Asad , Ali; Jamil, Salman (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate short-term outcomes and patient survival among kidney paired donation cases in living donor kidney transplants. Method: The retrospective, observational study was conducted in December 2024 at the Department of Kidney Transplantation Surgery, Pakistan Kidney and Liver Institute and Research Centre, Lahore, Pakistan, and comprised medical records of patients who underwent kidney paired donation living donor transplants from August 3, 2022, to July 9, 2024. Data included demographics, intraoperative and postoperative variables, delayed graft function, length of hospital stay, surgical site infection, rejection rates, graft survival and patient survival at one year. Data was analysed using SPSS 27. Results: Of the 28 subjects in 14 pairs, 20(71.4%) were females and 8(28.6%) were males. The overall mean age was 32.62±14.05 years and the median dialysis duration was 8 months (interquartile range: 10 months). The primary cause of end-stage renal disease among the recipients was unknown in 19(67.9%) cases. Postoperative creatinine levels were stable at 3, 6, 9 and 12 months, and there was only 1(3.6%) graft loss which was owing to acute T-cell-mediated rejection. No cases of delayed graft function and 30-day mortality were noted. Mean length of hospital stay was 6.62±1.50 days. There were 2(7.1%) cases facing complications, including surgical site infection and arterial anastomosis leakage. At 12 months, graft survival rate was 27(96.4%) and patient survival rate was 28(100%). Conclusion: Kidney paired donation in living donor kidney transplants demonstrated favourable short-term outcomes, with high graft survival and low complication rates. Key Words: Kidney paired donation, Living donor kidney transplant, Graft survival, Patient survival, Perioperative outcomes, Short-term outcomes, Kidney transplantation.